PERANCANGAN LOGO BUMI PERKEMAHAN BUKIT KABAYAN UNTUK VIDEO DOKUMENTER GAYA PERJALANAN - Davina Nurul Fadhilah; Ahmad Fuad (PT. Saha Kreasi Indonesia, 2026)
Bukit Kabayan, a natural tourist destination that offers a memorable camping experience, needs effective promotion to increase public awareness of its tourism potential. In this endeavor, the author designed a logo for Bukit Kabayan Campground that will be used in a documentary video to introduce the uniqueness and potential of this tourism to the public. The main objective of designing this logo is to create a strong and attractive visual identity that can be used in the documentary video. This logo must be able to describe the natural beauty of Bukit Kabayan and offer a unique and memorable camping experience. The method used by researchers is data collection such as observation, interviews, and also literature studies to add to the author's references regarding logos that are suitable for the visuals of Bukit Kabayan Campground.